Continuing versus withdrawing ixekizumab treatment in patients with axial spondyloarthritis who achieved remission: efficacy and safety results from a placebo-controlled, randomised withdrawal study (COAST-Y). Issue 8 (6th May 2021) - Landewé, Robert BM; Gensler, Lianne S; Poddubnyy, Denis; Rahman, Proton; Hojnik, Maja; Li, Xiaoqi; Liu Leage, Soyi; Adams, David; Carlier, Hilde; Van den Bosch, Filip
Abstract : Objectives: The objective of COAST-Y was to evaluate the effect of continuing versus withdrawing ixekizumab (IXE) in patients with axial spondyloarthritis (axSpA) who had achieved remission. Methods: COAST-Y is an ongoing, phase III, long-term extension study that included a double-blind, placebo (PBO)-controlled, randomised withdrawal-retreatment period (RWRP). Patients who completed the originating 52-week COAST-V, COAST-W or COAST-X studies entered a 24-week lead-in period and continued either 80 mg IXE every 2 (Q2W) or 4 weeks (Q4W). Patients who achieved remission (an Ankylosing Spondylitis Disease Activity Score (ASDAS)<1.3 at least once at week 16 or week 20, and <2.1 at both visits) were randomly assigned equally at week 24 to continue IXE Q4W, IXE Q2W or withdraw to PBO in a blinded fashion. The primary endpoint was the proportion of flare-free patients (flare: ASDAS≥2.1 at two consecutive visits or ASDAS>3.5 at any visit) after the 40-week RWRP, with time-to-flare as a major secondary endpoint. Results: Of 773 enrolled patients, 741 completed the 24-week lead-in period and 155 entered the RWRP. Forty weeks after randomised withdrawal, 83.3% of patients in the combined IXE (85/102, p<0.001), IXE Q4W (40/48, p=0.003) and IXE Q2W (45/54, p=0.001) groups remained flare-free versus 54.7% in the PBO group (29/53). Continuing IXE significantly delayed time-to-flare versus PBO, with most patients remaining flare-free for up to 20 weeks after IXE withdrawal. Conclusions: Patients with axSpA who continued treatment with IXE were significantly less likely to flare and had significantly delayed time-to-flare compared with patients who withdrew to PBO.